Contrasting population differentiation in two sympatric Triplophysa loaches on the Qinghai–Tibet Plateau - Jin, Ling; Li, Zitong; Wang, Chongnv; Wang, Yingnan; Li, Xinxin; Yang, Jian; Zhao, Yahui; Guo, Baocheng (Frontiers in Genetics, 2022)
Genetic differentiation in aquatic organisms is usually shaped by the drainage connectivity. Sympatric aquatic species are thus expected to show similar population differentiation patterns, and similar genetic responses to their habitats. Water bodies on the Qinghai-Tibet Plateau (QTP) has experienced dramatic physicochemical changes recently, which threaten the biodiversity of aquatic organisms on the ‘roof of the world’. To uncover ecological genetics in Tibetan loaches (Triplophysa) – the largest component of the QTP ichthyofauna, we characterized population differentiation patterns and adaptive mechanisms to salinity change in two sympatric and phylogenetically closely related Tibetan loaches, T. stewarti and T. stenura, by integrating population genomic, transcriptomic, and electron probe microanalysis approaches. Based on millions of genome-wide SNPs, the two Tibetan loach species show contrasting population differentiation patterns, with highly geographically structured and clear genetic differentiation among T. stewarti populations while no such observation in T. stenura, which is also supported by otolith microchemistry mapping. While limited genetic signals of parallel adaption to salinity changes between the two species are found from either genetic or gene expression variation perspective, a catalogue of genes involved in ion transport, energy metabolism, structural reorganization, immune response, detoxification, and signal transduction is identified to be related to adaptation to salinity change in Triplophysa loaches. Taken together, our findings broaden our understandings of the population characteristics and adaptive mechanisms in sympatric Tibetan loach species and would contribute to biodiversity conservation and management of aquatic organisms on the QTP.